2023
DOI: 10.3390/app13116791
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Green-Water Loads and Structural Responses of Ship Bow Structures Caused by Freak Waves

Abstract: In recent decades, freak waves, characterized by their unusual high amplitude, sharp crest, and concentrated energy, have attracted researchers’ attention due to their potential threat to marine structures. Green-water loads caused by freak waves can be significant and may lead to local damage to the ship structures. Therefore, this paper focuses on the study of green-water loads and examines the structural responses of ship bow structures under the influence of the green-water loads caused by freak waves. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Cao and Wen [4] combined the large eddy simulated turbulence model and Lighthill's acoustic analogy theory and extracted the transient flow field data as the excitation conditions for acoustic calculations. Zhang et al [5] examined the structural responses of ship bow structures under the influence of greenwater loads caused by freak waves with an unusually high amplitude and concentrated energy. In the field of marine technology, Carrillo-Aguilar et al [6] suggested algorithms to identify the dry fins of 37 shark species involved in the shark fin trade from 14 countries, which demonstrated a high sensitivity and specificity of image processing.…”
Section: Advances In Applied Marine Sciences and Engineeringmentioning
confidence: 99%
“…Cao and Wen [4] combined the large eddy simulated turbulence model and Lighthill's acoustic analogy theory and extracted the transient flow field data as the excitation conditions for acoustic calculations. Zhang et al [5] examined the structural responses of ship bow structures under the influence of greenwater loads caused by freak waves with an unusually high amplitude and concentrated energy. In the field of marine technology, Carrillo-Aguilar et al [6] suggested algorithms to identify the dry fins of 37 shark species involved in the shark fin trade from 14 countries, which demonstrated a high sensitivity and specificity of image processing.…”
Section: Advances In Applied Marine Sciences and Engineeringmentioning
confidence: 99%